2013
DOI: 10.2147/ijgm.s40001
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of symptoms and risk of sleep apnea in Dubai, UAE

Abstract: PurposeThe United Arab Emirates (UAE) ranks 18th on the 2007 Forbes list of fattest countries with 68.3% of its citizens with an unhealthy weight and it is well known that weight gain and obesity are important determinants in the progression of obstructive sleep apnea syndrome (OSAS). The purpose of this study is to estimate the prevalence of symptoms and risk of OSAS in the primary health care setting in Dubai, and the relationship between obesity and sleep apnea.MethodsIn this prospective survey, a trained m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 12 publications
0
11
1
Order By: Relevance
“…This male predominance can be due to gender differences in the tobacco smoking, alcohol use, adipose tissue distribution, upper airway anatomy and muscle function, control of ventilation, and the effects of sex hormones and leptin (10). In contrast to our study, three studies in conducted in the Middle East reported that female patients were more prone to sleep apnea (23–24, 27). These findings can be explained by the high prevalence of female obesity in that population (1, 2).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This male predominance can be due to gender differences in the tobacco smoking, alcohol use, adipose tissue distribution, upper airway anatomy and muscle function, control of ventilation, and the effects of sex hormones and leptin (10). In contrast to our study, three studies in conducted in the Middle East reported that female patients were more prone to sleep apnea (23–24, 27). These findings can be explained by the high prevalence of female obesity in that population (1, 2).…”
Section: Discussioncontrasting
confidence: 99%
“…Prevalence of high risk for OSA using Berlin questionnaire was 18%, and is higher than 10% reported from Pakistan, but it is comparable to 17.4% found in Southwestern Nigeria, 16.8% in Jordan and 20.9% in the United Arab Emirates (13,26,27). The prevalence of high risk for OSA is higher in the western world, as 26–36% was observed in the USA and Europe and 33–39% in Saudi Arabia (21, 23–24).…”
Section: Discussionmentioning
confidence: 46%
“…Recent study in Dubai on prevalence of OSA in UAE ( n = 1200 participants attending PHC clinics) revealed that almost 24% of males and 21% of females in the UAE probably have sleep disorders primarily related to OSAHS [12]. …”
Section: High Prevalence Of Obesitymentioning
confidence: 99%
“…There is sparse data regarding the prevalence of OSA in our region (Middle East). In a study of Saudi patients with renal disease, the prevalence of OSA was ~20% compared to 5 to 7% among the general population 8,9. Sleep disturbances is a major diagnostic criterion in many mental health disorders.…”
Section: Introductionmentioning
confidence: 99%